step 1; a=b step 2; a^2=ab (multiplying both sides by a) step 3; a^2-b^2=ab-b^2 (subtracting both sides by b^2) step 4; (a+b)(a-b)=b(a-b) step 5; (a+b)=b (cancelling (a-b) from both sides) step 6; 2b=b (as a=b from step 1) therefore, 2=1 (cancelling b from both the side)
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
step 5 is wrong because you are cancelling (a-b) from both sides which according to step 1 is equal to zero. Dividing by zero is incorrect.
Log in to reply
yes the step 5 is incorrect and the procedure includes diving by 0 i.e.(a-b) is absolutely wrong...leading to wrong result...:)
step 5 is wrong due to dividing by 0
thnx for answering